2000
DOI: 10.1159/000027766
|View full text |Cite
|
Sign up to set email alerts
|

Benign and Malignant Oncocytoma of the Salivary Glands with an Immunohistochemical Evaluation of Ki-67

Abstract: We present two cases of benign oncocytoma derived from the parotid gland and minor salivary gland and one case of malignant oncocytoma from the parotid gland. The proliferative activity of the tumor cells was evaluated immunohistochemically for Ki-67. The average frequency of Ki-67-positive cells was 3.3% in the benign oncocytomas and 6.5% in the malignant oncocytoma. The higher frequency of Ki-67-positive cells in the malignant oncocytoma might reflect active cell proliferation. Ki-67 immunostaining may be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…They concluded that ki-67 may assist in differentiating malignant from benign laryngeal epithelium lesions. A similar result was obtained by Ito et al [15] for distinguishing a benign oncocytoma from a malignant form. TLI is a kinetic parameter and radioactive thymidine incorporates into DNA in the S phase of the cell cycle so it is possible to determine the labeled proliferating cell ratio in a cell population [2].…”
Section: Discussionsupporting
confidence: 86%
“…They concluded that ki-67 may assist in differentiating malignant from benign laryngeal epithelium lesions. A similar result was obtained by Ito et al [15] for distinguishing a benign oncocytoma from a malignant form. TLI is a kinetic parameter and radioactive thymidine incorporates into DNA in the S phase of the cell cycle so it is possible to determine the labeled proliferating cell ratio in a cell population [2].…”
Section: Discussionsupporting
confidence: 86%
“…The prognostic importance of Ki67 has been emphasized in relation to various neoplasias, like prostate cancer [14], gastrointestinal stromal tumors [25], breast cancer [26], and parotid gland tumors [27]. Loro et al [28]compared Ki67 expression in snuff-using and non-snuff-using oral squamous cell carcinoma patients in Norway and Sudan.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the frequency of Ki-67-positive cells was significantly higher in malignant salivary gland tumours compared with that in benign tumours of the salivary gland. 7 Ito et al 8 also demonstrated that Ki-67 immunostaining was useful in distinguishing a benign from malignant oncocytoma.…”
Section: Discussionmentioning
confidence: 98%
“…Ito et al. 8 also demonstrated that Ki‐67 immunostaining was useful in distinguishing a benign from malignant oncocytoma.…”
Section: Discussionmentioning
confidence: 98%